Chuai duai!!! Fai mai mahadtai (Kruekhrai Dhammapiban, 2010)
Critique on the Ministry of Interior for its alleged inaction in response to the burning of three provincial administration buildings by the Red Shirts. The Ministry at the time was headed by the Bhumjai Thai Party, personified by the portrait of partyleader Newin Chidchob on the cover.